Microbial landscape features in patients with generalized periodontitis at pre-clinical and radiological stage of its development. - N. V. Vatamanyuk (Medičnì Perspektivi, 2014)
The paper presents the results of a comparative study of microbial landscape features in patients with generalized periodontitis at pre-clinical and radiological stage of its development in 42 patients. The purpose of the study is a comparative study of the composition of microbiocenosis of periodontal tissues in patients with chronic catarrhal gingivitis (CCG) and chronic generalized periodontitis (CGP) at an early stage of development and development studies of microbiological criteria for early emergence of the destructive process in periodontal structures. We found that the microflora isolated from dento-gingival grooves is of importance in diagnostics to identify the etiology of chronic generalized catarrhal gingivitis (CGCG) and chronic generalized periodontitis in the early stages of its development. It was established that the presence of two or more types of fixed parodonto-pathogenic microorganisms in microbial association increases the likelihood of inflammatory and destructive events in periodontal tissues in patients with GCCG and is one of the reasons of is becoming CGP.